Balancing CIK Cell Cancer Immunotherapy and PPAR Ligands: One Potential Therapeutic Application for CNS Malignancies - Kira Vordermark; JingJing Pu; Amit Sharma; Jarek Maciacyzk; Ingo G. H. Schmidt‐Wolf (Cancer Medicine)
ABSTRACT Background Cytokine‐induced killer (CIK) cell therapy has proven successful in clinical trials regarding glioblastoma. Equally important are the hints suggesting peroxisome proliferator‐activated receptors (PPARs) ligands being co‐expressed in the central nervous system (CNS). This provides a rationale about investigating the possible synergistic effect of CIK cells and PPARs. Methodology We investigated neuroblastoma and glioblastoma cell lines with mature CIK cells and the PPARγ antagonist GW‐9662 to assess the effects on cell viability, candidate gene expression (Wnt/β‐catenin signalling, DNMT1) and global methylation levels (5‐methylcytosine, LINE‐1). Results Using a clinical applicable PPAR‐γ inhibitor, we showed that (1) PPARγ‐antagonist GW‐9662 suppressed tumor cell growth in both neuroblastoma and glioblastoma cells, (2) PPARγ inhibition had restricted effect on the expression of Wnt/β‐catenin associated genes, (3) inhibition of PPARγ led to downregulation of DNMT1 expression, supporting their hypothesized interaction in cancer, (4) a partial modulation of global LINE‐1 methylation levels was observed, indicating their role in epigenetic processes, and (5) Combining PPARγ inhibition with CIK cell immunotherapy enhanced cell lysis significantly. Conclusion We provide evidence that PPAR ligands in combination with CIK cell immunotherapy could be a valuable option for malignant CNS tumors.